2000
DOI: 10.1016/s0014-5793(00)02095-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the dual coupling of the rat neurotensin receptor with pertussis toxin‐sensitive and insensitive G‐proteins

Abstract: We previously demonstrated the functional coupling of the rat neurotensin receptor NTS1 with G-proteins on transfected CHO cell homogenates by showing modulation of agonist affinity by guanylyl nucleotides and agonist-mediated stimulation of [ 35 S]GTPQ QS binding. In the present study, we observed that G iao -type G-protein inactivation by pertussis toxin (PTx) resulted in a dramatic reduction of the NT-induced [ 35 S]GTPQ QS binding whereas the effect of guanylyl nucleotide was almost not affected. As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…suggesting that this parameter mainly reflected nucleotide exchange at G i/o [20,53]. This result was confirmed by experiments with fusion proteins consisting of various G subunits covalently linked to rat NTS1 C-terminus [23].…”
Section: One Receptor One G Protein: Two Distinct Ways Of Influencinsupporting
confidence: 54%
See 2 more Smart Citations
“…suggesting that this parameter mainly reflected nucleotide exchange at G i/o [20,53]. This result was confirmed by experiments with fusion proteins consisting of various G subunits covalently linked to rat NTS1 C-terminus [23].…”
Section: One Receptor One G Protein: Two Distinct Ways Of Influencinsupporting
confidence: 54%
“…An involvement of these G proteins in the functional correlates of NTS1 receptor stimulation was also suggested by experiments showing that intracellular injection of an antibody against the common C-terminus of G q and G 11 inhibited the NT-induced alterations in function of ion channels [77]. However, NT was also found to induce inhibition of adenylyl cyclase and stimulation of arachidonic acid production through interaction with G i/o -type G proteins in selected systems, such as CHO cells transfected with rat or human NTS1 [20,53,56] and rat neuroblastoma N1E115 cell line [11]. Furthermore, this peptide stimulated adenylyl cyclase through interaction with G s in cells transfected with rat or human NTS1 [62,69,79] and in human pancreatic cancer cells endogenously expressing the receptor [31], but not in human colonic adenocarcinoma HT29 cells [1].…”
Section: One Pluripotent Receptor Several Cells: How To Combine Econmentioning
confidence: 89%
See 1 more Smart Citation
“…However, stimulation of this receptor also activated other pathways such as production of arachidonic acid or cAMP, through G i/o or G s , respectively (Yamada et al, 1993;Gailly et al, 2000). Although coupling to G q/11 was previously reported to involve the third intracellular loop of NTS1 receptor (Yamada et al, 1994), we recently demonstrated that coupling to G i/o involved the carboxy-terminal portion of this receptor (Najimi et al, 2002).…”
mentioning
confidence: 55%
“…Activation of rat NTR1 (rNTR1) induces an increase in inositol trisphosphate (IP 3 ) and Ca 2+ mobilization through an activation of G q/11 (Watson et al 1992, Chabry et al 1994, Hermans et al 1994. It has also been reported that stimulation of NTR1 evokes the production of arachidonic acid and cAMP through G i/o and G s activation respectively (Yamada et al 1993, Carraway & Mitra 1998, Gailly et al 2000. Furthermore, levocabastine and SR 48692 trigger Ca 2+ mobilization, IP production, arachidonic acid release and mitogenactivated protein kinase activity in CHO cells expressing rNTR2 or hNTR2 , Yamada et al 1998.…”
Section: Introductionmentioning
confidence: 99%